Dr. Tom Shinder's ISA server 2006 migration guide - Shinder, Thomas W.; Shinder, Debra Littlejohn; Dimcev, Adrian F. (Syngress Pub., 2007)
Dr. Tom Shinder's first 2 books on configuring ISA Server have sold more than 50,000 units worldwide!